EFFECT OF THE PHOTO-FENTON PROCESS ON ASCARIS HELMINTH EGGS AND BACTERIAL GROWTH IN THE WASTEWATER TREATMENT PLANT IN HILLA-BABYLON PROVINCE, IRAQ - Mohammed H. K. AL Mayali; Atheer S. N. Al-Azawey (Web of Journals Publishing, 2024)
In this study, one of the photo-oxidation techniques (Fenton Photo) was used to inactivate Ascaris helminth eggs and bacterial growth sampled in a wastewater treatment plant in Al-Hilla City, which is considered an indicator of pollution and restricts water use. Fenton Photo technology relies on the formation of free radicals, such as hydroxyl radicals, through the use of ultraviolet radiation from sunlight, as well as the use of peroxide as a catalyst and iron oxides as an oxidizing agent. The effect of treatment time on the percentage of removal efficiency (R.E.%) for eggs and bacterial growth rate was studied. The average of R.E% was 69.40% at treatment time 15 minute ,89.73% at treatment time 30 minute, and 100% at treatment time 40 minute. The removal efficiency of bacteria was 100% at all treatment times.
Keywords: Wastewater, treatment, bacteria, helminthes, photooxidation.